Evidence of somatic hypermutation in the antigen binding sites of patients with CLL harboring IGHV genes with 100% germline identity - Sofou, Electra; Zaragoza-Infante, Laura; Pechlivanis, Nikolaos; Karakatsoulis, Georgios; Notopoulou, Sofia; Stavroyianni, Niki; Psomopoulos, Fotis; Georgiou, Elisavet; de Septenville, Anne Langlois; Davi, Frederic; Agathangelidis, Andreas; Chatzidimitriou, Anastasia; et al. (Frontiers in Oncology, 2022)
Classification of patients with chronic lymphocytic leukemia (CLL) based on the somatic hypermutation (SHM) status of the clonotypic immunoglobulin heavy variable (IGHV) gene has established predictive and prognostic relevance. The SHM status is assessed based on the number of mutations within the IG heavy variable domain sequence, albeit only over the rearranged IGHV gene excluding the variable heavy complementarity determining region 3 (VH CDR3). This may lead to an underestimation of the actual impact of SHM, in fact overlooking the most critical region for antigen-antibody interactions, i.e. the VH CDR3. Here we investigated whether SHM may be present within the VH CDR3 of cases bearing ‘truly unmutated’ IGHV genes (i.e. 100% germline identity across VH FR1-VH FR3) employing Next Generation Sequencing. We studied 16 patients bearing a ‘truly unmutated’ CLL clone assigned to stereotyped subsets #1 (n=12) and #6 (n=4). We report the existence of SHM within the germline-encoded 3’IGHV, IGHD, 5’IGHJ regions of the VH CDR3 in both the main IGHV-IGHD-IGHJ gene clonotype and its variants. Recurrent somatic mutations were identified between different patients of the same subset, supporting the notion that they represent true mutational events rather than technical artefacts; moreover, they were located adjacent to/within AID hotspots, pointing to SHM as the underlying mechanism. In conclusion, we provide immunogenetic evidence for intra-VH CDR3 variations, attributed to SHM, in CLL patients carrying ‘truly unmutated’ IGHV genes. Although the clinical implications of this observation remain to be defined, our findings offer a new perspective into the immunobiology of CLL, alluding to the operation of VH CDR3-restricted SHM in U-CLL.